Síntese e Atividade Alelopática de Carboxamidas Indólicas - Thiago Freitas Borgati (2010)
This work describes the preparation of five amides from indole-3-carboxilic acid (1) with one monoamide and 4 symmetric diamines, to evaluate their activities as allelopathic and antimicrobial agents and to calculate their nbutanol- water partition coefficient (P).Initially, in a General Introduction, Chapter 1, a bibliographic review onindole alkaloids and allelopathy is done. Chapter 2 (Results and Discussion) describes the spectrometric analysis of synthesized amides by IR, 1H and 13C NMR and MS. The obtained amide from monoamine was: N-(morpholin)-1H-indole-3-carboxamide (2). The obtained amides from symmetric diamines were: N-(piperazin)-1H-indole-3- carboxamide (3), N-(2-aminoethyl)-1H-indole-3-carboxamide (4), N-(3- aminopropyl)-1H-indole-3-carboxamide (5) and N-(4-aminobutyl)-1H-indole-3- carboxamide (6).All monoamides are described here for the first time, except the onederived from morpholin (2). Chapter 3 (Experimental Part) describes the methodology to obtain the above amides. In Chapter 4, the results obtained from biological evaluation, antimicrobial and allelopathic tests, and the calculated log P are presented.